Integrative Leadership of Kyai in Improving the Quality of Education: Case Study at Raudhatul Ulum Guyangan Pati Islamic Boarding School - Abd Azis; Yahya, Imam; Sukendar (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2025)
This study aims to describe the management of Raudhatul Ulum Guyangan Pati Islamic boarding school through an integrative leadership model. This research includes field research with a qualitative descriptive approach by making the kyai as the primary data source. Meanwhile, secondary data were collected from the vice kyai, RSA director, teachers and head of administration. Data were collected using interview techniques (structured), observation and documentation. After the data is collected, it is then analyzed by reducing the data, then displaying the data and before concluding, data verification is carried out first to ensure the validity of the data. This study concludes that through integrative leadership, and by implementing the three dimensions of integrative leadership, namely tasks, relationships and changes, caregivers are able to bring PPRU as the most qualified educational institution in the Pati region by achieving educational quality indicators, namely effectiveness, efficiency, equality and satisfaction